The Triumph of Virtual Reality - McLaren, Glenn (Cosmos and History: The Journal of Natural and Social Philosophy, 2012)
<!--[if gte mso 9]> <![endif]--><!--[if gte mso 9]> Normal 0 false false false EN-US X-NONE X-NONE <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <![endif]-->Where will the philosophers of the future come from and can we have civilization without them? In this paper I argue that there is a co-dependent relationship between philosophy and civilization, one that has emerged and developed in relation to the emergence of information technologies, particularly writing and print and conditions for deep and prolonged concentration. The internet, however, today's powerful information technology which is increasingly mediating humanities relationships, is proving to be a technology which threatens this relationship. The internet is a technology which draws us in, obliterating the distance required for critical thought. Unless we can find ways to distance ourselves from this technology, this creator of high fidelity virtual realities, we will become trapped in our hi-tech representations. This will be the triumph of virtual reality and perhaps the end of civilization and philosophy.